Pengaruh Kombinasi BAP (Benzyl Amino Purine) dan Kinetin Terhadap Multiplikasi Tunas Tanaman Tebu (Saccharum officinarum L.) Varietas AAS Agribun - Ramadhan, Mochamad Alif; Bayfuqron, Fawzy Muhammad; Saputro, Nurcahyo Widyodaru; Suhesti, Sri (UNIVERSITAS LABUHANBATU, 2024)
Sugarcane (Saccharum officinarum L.) is a plantation commodity crop and raw material for making sugar. The need for sugar increases every year so it is necessary to provide superior sugarcane seeds in large quantities in a relatively short time. This can be done by propagating using the plant tissue culture method. The research method used was an experimental method using a combined Completely Randomized Design (CRD) with 4 replications and 8 treatments consisting of: Control (P0); 0.5 ppm BAP + 0 ppm kinetin (P1); 1 ppm BAP + 0 ppm kinetin (P2); 2 ppm BAP + 0 ppm kinetin (P3); 0 ppm BAP + 0.1 ppm kinetin (P4); 0.5 ppm BAP + 0.1 ppm kinetin (P5); 1 ppm BAP + 0.1 ppm kinetin (P6); and 2 ppm BAP + 0.1 ppm kinetin (P7). The data then explained the variations and then continued with the DMRT test at the 5% level. The results showed that treatments P3 and P7 showed the best results at the time of shoot emergence. The P3 treatment also showed the best results in the number of shoot (8.25) and number of leaves (16.50). The P7 treatment showed the highest shoot yield (4.58). Keywords: sugarcane, BAP, kinetin, shoot multiplication